The Effectiveness of Training Critical Thinking Skills on Students' Attitude towards Substance Abuse - Afsar Khalili; Faramarz Sohrabi; Mohammad hasan Radmanesh; Mahdi Afkhami (Drug Control Headquarters, Research and Education Office, 2011)
Introduction: The purpose of this study was to determine the effectiveness of critical thinking training on Students, attitude towards substance abuse in high school students of Yazd city. Method: The research method was experimental design (with experimental and control group). The population of this research was the first grade of high school boy students of Yazd city. From all high school students in Yazd city, 40 students were selected by clustering random sampling, 20 students for each group, and attitude toward substance abuse questionnaire administered among selected sample for two times (pre-test and post-test). Critical thinking training, presented to students who assigned to experimental group for eight, 90 minutes sessions, every week one session. Also there were not presented any treatment to control group and they were waiting for training. After finishing of training, post test administered among both groups. Analysis of covariance (ANCOVA) and Leven's tests were used to determine the effectiveness of training intervention. Results: The results of this research showed that there is homogeneity of variance. Also, the Covariance test showed significant effect of critical thinking training. Conclusion: The results indicated that critical thinking training was effective for changing students' attitude toward substance abuse.